Combined effect of cold atmospheric plasma, intrinsic and extrinsic factors on the microbial behavior in/on (food) model systems during storage. (May 2019) - Smet, C.; Baka, M.; Steen, L.; Fraeye, I.; Walsh, J.L.; Valdramidis, V.P.; Van Impe, J.F.
Abstract: Microbial decontamination by means of cold atmospheric plasma (CAP) offers great potential for treatment of heat-sensitive food products, extending their storage life. CAP is created by applying a high voltage to a gas stream, resulting in microbial inactivation according to different mechanisms. This paper thoroughly assesses the influence of CAP on the storage life of food model systems inoculated with Salmonella Typhimurium. (Food) model systems, with varying intrinsic factors (pH, salt concentration, and food (micro)structure), are treated for 5 min using a dielectric barrier discharge reactor generating a helium‑oxygen plasma. Following treatment, the impact of extrinsic factors is evaluated by storage at 8 °C or 20 °C. During storage, cell densities are determined. Data are fitted with predictive (growth or inactivation) models. As additional experiments indicate that the CAP treatment itself has a limited or even negligible effect on the properties of the model system (pH, aw, (micro)structure), the microbial behavior of CAP treated samples during storage can be attributed to the treatment. CAP treatment can result in microbial reductions up to 2.7 log10 and prolongs storage, however its rate of success is dependent on both extrinsic and intrinsic factors. An important factor is the storage temperature, as recovery of CAP treated cells proves more difficult when stored at 8 °C. At 20 °C, cell growth is merely slowed down. Additionally, at pH 5.5, 6% ( w / v ) NaCl, osmotic stress is induced on the microorganisms, which results in low cell recovery or further inactivation. The influence of the food (model) structure on the storage behavior is insignificant. Industrial relevance: Although being a very promising technology, most studies regarding the use of cold atmospheric plasma (CAP) for food decontamination focus on the inactivation of a target microorganism, in relation to a specific food product. Fundamental knowledge on this non-thermal technology, including its impact on the storage life, is lacking. This study investigates the effect of CAP on the microbial behavior during storage. By performing tests on model systems, for a variation of intrinsic and extrinsic factors, this work renders information on the suitability of this novel technology regarding treatment of a broad spectrum of food products. Moreover, this study demonstrates the limited impact of CAP on the food (model) properties, enhancing the suitability of the technology to be implemented in the food industry. Highlights: CAP treatment potentially significantly extends the storage life of a product. Intrinsic (model system) and extrinsic factors (storage temperature) influence microbial kinetics after CAP treatment. Synergistic antimicrobial effect due to storage at low temperatures after CAP treatment. Stressing model system properties magnify the efficacy of the treatment.